2006
DOI: 10.1016/j.ejheart.2005.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Stress and tissue Doppler echocardiographic evidence of effectiveness of myoblast transplantation in patients with ischaemic heart failure

Abstract: Background: There is experimental evidence that transplanting skeletal myoblasts (SM) into the post-infarction myocardial scar improves regional and global left ventricular (LV) function. Aims: To evaluate short-and long-term regional and global LV functional effects of percutaneously transplanted SM in patients with ischaemic heart failure. Methods and results: Ten patients (mean age 60 T 10 years, 8 males) with dilated ischaemic cardiomyopathy underwent percutaneous injection of autologous myoblasts. Regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 30 publications
2
18
0
1
Order By: Relevance
“…Interestingly, the extent of functional improvement did not correlate with the number of cells injected. Two additional trials have utilized endoventricular catheters to introduce cells during electromechanical mapping [Brasselet et al, 2005;Biagini et al, 2006]. Both studies reported an improvement in regional and/or global LV function up to 1 year after cell transfer, although no data demonstrating stable SMB engrafted was presented.…”
Section: Smb Transplantation From Bench To Bedsidementioning
confidence: 99%
“…Interestingly, the extent of functional improvement did not correlate with the number of cells injected. Two additional trials have utilized endoventricular catheters to introduce cells during electromechanical mapping [Brasselet et al, 2005;Biagini et al, 2006]. Both studies reported an improvement in regional and/or global LV function up to 1 year after cell transfer, although no data demonstrating stable SMB engrafted was presented.…”
Section: Smb Transplantation From Bench To Bedsidementioning
confidence: 99%
“…Experimentally, myoblasts engraft in postinfarction scars, differentiate into myotubes, and improve LV function (reviewed in Dowell et al 1 ). The consistency and robustness of these results have paved the way for the first surgical [2][3][4][5][6] or catheter-based [7][8][9] phase I trials, which have confirmed feasibility but by virtue of design could not fully evaluate efficacy and safety profiles. We therefore implemented the Myoblast Autologous Grafting in Ischemic Cardiomyopathy (MAGIC) trial to specifically address these issues.…”
mentioning
confidence: 99%
“…Also, in vivo experiments in rats showed the same cell-dose dependency [78]. In patients, although some cases of arrhythmias have been reported, overall, an improvement in the cardiac function together with an increase in the viability and perfusion has been found in most of the clinical trials published so far [79] [76] [80][81][82][83][84][85]. Some studies like that published by Gavira et al have been successful with no cardiac arrhythmia reported after one-year follow-up [80].…”
Section: Clinical Trials Using Skeletal Myoblastsmentioning
confidence: 75%
“…Interestingly, cells were delivered percutaneously, so the feasibility and safety of this route of transplantation were confirmed [86]. A second study was also performed by the group led by Serruys [79] proving also the safety of the method and documenting an increase in the global ejection fraction. Although all these data are quite suggestive, the small number of patients included in these studies as well as the lack of placebo groups make it impossible to draw any definitive conclusion regarding the beneficial effect of this approach.…”
Section: Clinical Trials Using Skeletal Myoblastsmentioning
confidence: 99%